Association between life’s essential 8 and testosterone deficiency in men: NHANES 2011–2016 - Cai, Min; Chen, Jinzao (Frontiers in Endocrinology, 2024)
Serum testosterone is intrinsically associated to cardiovascular disease. Our aim is to explore the relationship between the recently updated cardiovascular health measurement, known as Life's Essential 8 (LE8), and the prevalence of testosterone deficiency (TD) in adult males in the United States.Study data was obtained from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016. A weighted multivariate logistic regression model was applied to evaluate the correlation between LE8 and testosterone deficiency.Restricted Cubic Spline (RCS) was employed to explore its non-linear relationship. In addition, a stratified analysis was conducted.The final analysis included 2362 participants from NHANES from 2011 to 2016.After adjusting for confounding factors, the odds ratios (ORs) and 95% confidence intervals (CIs) for testosterone deficiency in participants with moderate and higher LE8 scores compared to the lowest LE8 scores were 0.59 (0.38-0.92) and 0.38 (0.19-0.76), respectively. The results of subgroup analysis showed that LE8 score was significantly associated with TD among young and middle-aged participants.A lower LE8 score is related to a higher incidence of testosterone deficiency, especially in young and middle-aged men. Further research is necessary to explore the potential mechanisms between them.